The Ethics of Research with Human Subjects Protecting People, Advancing Science, Promoting Trust - Resnik, David B. (International Library of Ethics, Law, and the New Medicine,, 2018)
This book provides a framework for approaching ethical and policy dilemmas in research with human subjects from the perspective of trust. It explains how trust is important not only between investigators and subjects but also between and among other stakeholders involved in the research enterprise, including research staff, sponsors, institutions, communities, oversight committees, government agencies, and the general public. The book argues that trust should be viewed as a distinct ethical principle for research with human subjects that complements other principles, such as autonomy, beneficence, non-maleficence, and justice. The book applies the principle of trust to numerous issues, including informed consent, confidentiality, risk minimization, risks and benefits, protection of vulnerable subjects, experimental design, research integrity, and research oversight.This work also includes discussions of the history of research involving human subjects, moral theories and principles, contemporary cases, and proposed regulatory reforms. The book is useful for undergraduate and graduate students studying ethical policy issues related to research with human subjects, as well as for scientists and scholars who are interested in thinking about this topic from the perspective of trust.